Modulation of heme oxygenase-1 by metalloporphyrins increases anti-viral T cell responses. (2nd January 2015) - Bunse, C E; Fortmeier, V; Tischer, S; Zilian, E; Figueiredo, C; Witte, T; Blasczyk, R; Immenschuh, S; Eiz-Vesper, B
Summary: Heme oxygenase (HO)-1, the inducible isoform of HO, has immunomodulatory functions and is considered a target for therapeutic interventions. In the present study, we investigated whether modulation of HO-1 might have regulatory effects on in-vitro  T cell activation. The study examined whether: (i) HO-1 induction by cobalt-protoporphyrin (CoPP) or inhibition by tin-mesoporphyrin (SnMP) can affect expansion and function of virus-specific T cells, (ii) HO-1 modulation might have a functional effect on other cell populations mediating effects on proliferating T cells [e.g. dendritic cells (DCs), regulatory T cells (Tregs ) and natural killer cells] and (iii) HO-1-modulated anti-viral T cells might be suitable for adoptive immunotherapy. Inhibition of HO-1 via SnMP in cytomegalovirus (CMV)pp65-peptide-pulsed peripheral blood mononuclear cells (PBMCs) led to increased anti-viral T cell activation and the generation of a higher proportion of effector memory T cells (CD45RA − CD62L − ) with increased capability to secrete interferon (IFN)-γ and granzyme B. Treg depletion and SnMP exposure increased the number of anti-viral T cells 15-fold. To test the possibility that HO-1 modulation might be clinically applicable in conformity with good manufacturing practice (GMP), SnMP was tested in isolated anti-viral T cells using the cytokine secretion assay. Compared to control, SnMP treatment resulted in higher cell counts and purity without negative impact on quality and effector function [CD107a, IFN-γ and tumour necrosis factor (TNF)-α levels were stable]. These results suggest an important role of HO-1 in the modulation of adaptive immune responses. HO-1 inhibition resulted in markedly more effective generation of functionally active T cells suitable for adoptive T cell therapy.